ESTIMATION THE EFFICIENCY OF FUNCTIONING THE FINANCIAL MECHANISM OF STATE REGULATION OF SOCIO-ECONOMIC DEVELOPMENT - И. М. Шаповалова (Science and Innovation Center Publishing House, 2014)
In modern conditions, when all political units are charac-terized with the different level of socio-economic development, a research of problem of estimation the efficiency of functioning the financial mechanism of state regulation of socio-economic development is very important, as the efficiency of functioning of the system is a base for acceptance administrative decisions, directed on achievement stably high level of socio-economic development of the country and its regions. Different concepts for the term «efficiency» were reviewed. A definition of the term «efficiency of functioning of the financial mechanism of state regulation of socio-economic development» was proposed, as a reflection of ability the present financial mechanism to support the balance in all sectors of economy, to provide realization of available potential and concordance of national and regional interests. Methods of estimation the efficiency of functioning of fi-nancial mechanism of state regulation of socio-economic deve-lopment was offered with the use of the developed normative indexes, characterizing the level of development. The estimation the efficiency of functioning of financial me-chanism of the regions in Autonomous Republic of Crimea was conducted. The analysis revealed that at the level of Autonomous Republic of Crimea, as well as at national level, substantial lag of development in innovative-investment sector takes place simultaneously with the sufficient level of development of other sectors in most regions. In addition, the extremely low level of balance in financial mechanism takes place, therefore the financial mechanism of regions in Autonomous Republic of Crimea can not be considered as effectively functioning, that requires acceptance of urgent measures, directed on stimulation of socio-economic development. Purchase on Elibrary.ru > Buy now